Cerebral Blood Flow in Patients With Peritoneal Dialysis by an Easy Z‐Score Imaging System for Brain Perfusion Single‐Photon Emission Tomography. Issue 3 (June 2014) - Isshiki, Rei; Kobayashi, Shuzo; Iwagami, Masao; Tsutumi, Daimu; Mochida, Yasuhiro; Ishioka, Kunihiro; Oka, Machiko; Maesato, Kyoko; Moriya, Hidekazu; Ohtake, Takayasu; Hidaka, Sumi
Abstract Cognitive impairment has long been recognized as a complication of chronic kidney disease. However, there is little information available regarding regional cerebral blood flow (rCBF) in patients with peritoneal dialysis (PD). Therefore, we evaluated rCBF using brain single photon emission computed tomography (SPECT). We conducted a cross‐sectional study in our hospital. Eighteen consecutive PD patients who could visit the hospital by themselves without any history of stroke were examined by Technetium‐99 m‐labeled ethylcrysteinate dimer brain SPECT. An easy Z‐score imaging system (eZIS) was used to compare rCBF in PD patients with those in age‐matched healthy controls. We also evaluated cognitive dysfunction with the mini‐mental state examination (MMSE) questionnaire. Only one patient showed an MMSE score of 18 points, and the remaining 14 patients were considered as normal (MMSE ≥ 27), and three patients were considered to have mild cognitive impairment (24 ≤ MMSE ≤ 26). In all patients, rCBF in the posterior cingulated gyri, precunei, and parietal cortices was significantly decreased. The ratio of the reduction of rCBF in each region relative to that of rCBF across the whole brain correlated positively with the PD duration (r = 0.559; P < 0.05). The serum β2‐microglobulin level was significantly higher in patients who had a higher ratio of rCBF reduction compared with those with lower ratios. In conclusion, all PD patients in the present study had decreased rCBF irrespective of MMSE scores.